Integrasi Green Architecture dalam Rancangan Pusat Pendidikan dan Simulasi Bencana di Kawasan Tropis - Nabila Nur Mustafa; Zuhriati A. Djailani; Niniek Pratiwi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Gorontalo Province is an area with a high level of disaster vulnerability, both from hydrometeorological disasters such as floods and landslides, as well as geological disasters such as earthquakes. This condition requires an integrated, modern, and sustainable disaster training facility. Unfortunately, until now Gorontalo does not have a representative disaster management education and training center to support community preparedness. This research aims to design a Disaster Management Education and Training Center that not only functions as an education and simulation place, but also integrates green architecture principles to create an environmentally friendly and energy-efficient learning environment. The method used is qualitative descriptive with primary data collection through observation, interviews with stakeholders, and field documentation. Secondary data were obtained from literature studies, disaster architectural precedents, and spatial planning regulatory studies. The design site was chosen in Limboto District with considerations of accessibility, development potential, and geographical conditions. Analysis is carried out on spatial, functional, and climatological aspects to produce an optimal zoning concept and the orientation of building masses according to the tropical climate. The design results show that an area of 19,371 m² can accommodate all space needs with the utilization of KDB of 25.4%. The application of green architecture is realized through the use of environmentally friendly local materials, natural lighting, cross ventilation, solar panels, and rainwater management systems. The simulation facilities for floods, landslides, earthquakes, and fires are designed based on experiential learning so that participants can experience disaster scenarios firsthand. This design is expected to be a model of sustainable tropical disaster architecture, replicate in other disaster-prone areas, and encourage the creation of a disaster-aware culture. This research also opens up further research opportunities related to energy performance evaluation and the application of digital technology in disaster education.